Seeking underground for potential heat sink in Malaysia for Earth air heat exchanger (EAHE) application - Sanusi, Aliyah Nur Zafirah; Shao, Li; Ahmad Zamri, Aidil Azlan (PAK Publishing Group, 2014)
Prior to the exploration of technology for thermal comfort in Malaysia, this study investigates Malaysia soil temperature to demonstrate the potential of applying the technology in Malaysia. This preliminary investigation is significant since the EAHE technology utilizes the underground earth soil as a heat sink in warm climate countries. The EAHE technology has been applied successfully for cooling means in various building typologies in temperate as well as hot and arid countries. However, there is little published data on EAHE operation in hot and humid countries such as Malaysia. The main factor that could give positive result to EAHE cooling technology is the temperature difference between ambient and soil temperature. This paper presents measurements of air temperature and soil temperature at various depths up to 5m underground in a month of October and November in Kuala Lumpur. The field measurement was extended further measuring soil temperature at shallow depths in one year, measured on the same site. The result shows that at 1 meter underground, the soil temperature is approximately 7oC lower than the maximum air temperature, which was 34oC. Therefore, used properly in appropriate application, the EAHE cooling technology may be economically significant in a period with escalating energy cost and global warming.